A Case Series of Intraluminal Migration Gossypiboma in Regional Hospital of Maradi - Adakal, Ousseini; Mohamed, Rouga Moumouni; Abdoulaye, Maman Bachir; Adamou, Harissou; Magagi, Ibrahim Amadou; Didier, Lassey James; Sani, Rachid (European Scientific Journal, ESJ, 2019)
Introduction: Textiloma or Gossypiboma is used to describe a foreign body composed of a compress (s) or surgical field (s) forgotten at an operating site. Case report: Authors reported two cases of intestinal migrant textiloma in patients all previously operated on by cesarean section. The two patients consulted for a chronic painful abdominal mass. Abdominal ultrasound showed a superficial anterior structure in favor of foreign body in the first patient. The second one concluded that there was a right ovarian cyst. The surgery discovered a greek mass in both cases. Resection of the intestinal mass was performed followed by end to end anastomosis. The enterostomy of hail mass revealed an abdominal compress in each case. Conclusion: Forgetting a compress or abdominal field during surgery is a tragedy for the surgeon not only because of its forensic aspect but also because of the suffering endured by the patient. Indeed, actions trying to prevent this type of error are implemented in most developed countries; it is time for each hospital to adopt preventive measures, even if just only the compresses counting during the procedure.